2020
DOI: 10.3390/pharmaceutics12111016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Local Minocycline Agents in Treating Peri-Implantitis: An Experimental In Vivo Study in Beagle Dogs

Abstract: Background: Local delivery agents (LDA) have the advantage of delivering the antibiotics at high concentrations to the targeted sites. However, the constant flow of gingival crevicular fluids and saliva may restrict their efficacy. Therefore, the drug sustainability and pharmacodynamic properties of any proposed LDA should be evaluated. Methods: Four dental implants were placed unilaterally in the edentulous mandible of six beagle dogs. Peri-implantitis were experimentally induced using silk-ligatures. Each im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…44,45 Among the disinfection processes for this surface, PDT and antibiotic substitutes such as chitosan have recently emerged as promising options for antibacterial treatment and for reducing lipopolysaccharide and, therefore, cell titanium adherence. 32,41 In our study, for all the bacteria studied, PDT induced a lower viable cell count, higher percentage of cells with abnormal morphology, and higher percentage of no bacteria attached to the titanium surface than the control group, with statistically significant differences. As regards S. aureus, Widodo et al, (2016) 46 evaluated the efficacy of different methods (rinsing with PBS or control group, rinsing with 0.2%, chlorhexidine digluconate PDT, the use of cotton pellets, titanium brushes, or titanium brush and PDT) for the decontamination of titanium disc.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…44,45 Among the disinfection processes for this surface, PDT and antibiotic substitutes such as chitosan have recently emerged as promising options for antibacterial treatment and for reducing lipopolysaccharide and, therefore, cell titanium adherence. 32,41 In our study, for all the bacteria studied, PDT induced a lower viable cell count, higher percentage of cells with abnormal morphology, and higher percentage of no bacteria attached to the titanium surface than the control group, with statistically significant differences. As regards S. aureus, Widodo et al, (2016) 46 evaluated the efficacy of different methods (rinsing with PBS or control group, rinsing with 0.2%, chlorhexidine digluconate PDT, the use of cotton pellets, titanium brushes, or titanium brush and PDT) for the decontamination of titanium disc.…”
Section: Discussionmentioning
confidence: 47%
“…Although in the scientific literature there is no article with which we can compare our results on the bacteria S. aureus, E. coli, and P. aeruginosa; its effectiveness in the treatment of peri-implantitis has been investigated in the last 10 years. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In 2020, Yoon et al, 32 evaluated the treatment efficacies of two different local delivery agents (chitosan-alginate minocycline, and poilyacrylate-glycerin minocycline) compared with untreated control implants, in an experimentally induced peri-implantitis study in beagle dogs. The authors concluded that the use of chitosan-alginate minocycline as a local delivery agent constituted an effective treatment for peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotics alone do not clean the surface, and there is growing concern that microbial resistance might render these agents inefficient in the long term. Guidelines on the use of antibiotics, mainly systemic, now only recommend them as a last resort against more severe cases of infections, but there is a lack of clinical evidence showing antibiotics have any effect at all on the long-term outcome of peri-implant conditions (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%